2005 IEEE Pulsed Power Conference 2005
DOI: 10.1109/ppc.2005.300786
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Current Filaments in Photoconductive Semiconductor Switches

Abstract: Photoconductive semiconductor switches (PCSS's), such as optically-triggered GaAs switches, have been developed for a variety of applications. Such switches exhibit unique properties as a consequence of lock-on, a phenomenon associated with the bistable switching of these devices. In this paper, lock-on is explained in terms of collective impact ionization. Furthermore, the effect of defects on the performance of these devices is investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…A review on this work can be found in [200,204]; for later efforts, see, e.g. [206,211,368,369]. However, there is little work where a thorough quantitative comparison between theory and Table 11.…”
Section: Semiconductorsmentioning
confidence: 99%
“…A review on this work can be found in [200,204]; for later efforts, see, e.g. [206,211,368,369]. However, there is little work where a thorough quantitative comparison between theory and Table 11.…”
Section: Semiconductorsmentioning
confidence: 99%
“…The growing dipole domains can be fonned in this activated local region [5,6] if the product of excess carr ier density npe times the characteristic length LE of the illuminated region is larger than 10 12 cm -2 [9] and the localized electric field is in the region of negative differential mobility (NDM). If the growing domain accumulates carr iers and enables the carrier density to exceed nc ;::: :; 10 17 cm-3, the local electrical breakdown can arise because impact ionization is increased [10,11]. The avalanche breakdown can cause an S-shaped NDC [12,13], that is, the avalanche breakdown can complete a transition from N-to S-shaped NDC in this local region, current fil aments will therefore fonn [5].…”
Section: Development Of the Localized S-shaped Ndcmentioning
confidence: 99%
“…1) is in the region of NDM, the second generation growing domains can be fonned. In the growing domains, as soon as the accumulated carrier density exceed nc ;::: :; 10 17 cm -3, the collective impact ionization (Cll) mechanism[10,11] produces rapid avalanching to streamer conditions, thus advancing the filamentary structure. As described above, the rapid avalanching causes and completes the transition from the N-to S-shaped NDC in this activated local region.…”
mentioning
confidence: 99%
“…The time-dependent continuum calculations focus on the transport of electrons and holes during electrical breakdown [10]. The calculations focus on kinetic equations for electrons and holes.…”
Section: Continuum Calculations and Modelsmentioning
confidence: 99%
“…In a previous paper, one such model has been described and used [10]. In this paper, a new continuum model is described.…”
Section: Continuum Calculations and Modelsmentioning
confidence: 99%